RESEARCH ON THE IMPACT OF VIDEO GAMES ON ADOLESCENT BEHAVIOR USING DATA MINING TECHNIQUES - Chi Trung, Nguyen; Duy Trung Anh, Nguyen; Hai Tiep, Dao; Tho Hoan, Pham (HNUE Journal of Science: Journal of Educational Science, 2024)
The paper investigates and analyzes data regarding the effects of video games on adolescents’ learning, skill development, and social interaction to understand the current situation and propose corresponding solutions for this age group. It examines four factors (learning, social interaction, skill development, and personal behavior) by applying the Theory of Planned Behavior and the Theory of Reasoned Action to clarify their relationship with video gaming. Additionally, the survey data is analyzed using data mining techniques (data visualization) to analyze the survey results more deeply. The findings indicate that the investigated factors are closely correlated, with the impact on learning being considered the most significant influence.